The past, present and future of the non-traded NAV REIT structure. Issue 2 (4th December 2020) - Roberts, David H.; Santucci, Ettore A.; Schonberger, Mark; Lavigne, Peter W.
Abstract : Purpose: Over 15 years ago Goodwin created the first open-ended, non-traded real estate investment trust (REIT) with regular sales and redemptions at net asset value ("NAV REIT"). While NAV REITs are now well established, there is still room for improvement. Design/methodology/approach: We traced the evolution of the NAV REIT's innovative, investor-friendly features – transparent valuation to strike NAV, liquidity via redemption at NAV per share, indefinite life, lower/simpler selling and management fees, share classes with different upfront loads and trailing distribution fees. Findings: To improve the liquidity feature of NAV REITs, share classes could be used to lower the drag on performance and match available liquid assets with expected redemption requests. The goal: balance inflows and outflows, optimize portfolio construction, and better safeguard liquidity. Practical implications: One need not look far for the dark side of liquidity in open-ended real estate funds. The UK experience with regulated property funds is a painful object lesson. There is a better way: while traditional non-traded REITs were designed and marketed for investment by retail investors, NAV REITs appeal to a diverse range of investors, and share classes could be enhanced to offer both a menu of selling loads and a menu of liquidity and dividend-rate options to produce a smooth curve blending cost and time. Originality/value: Innovation in structuring real estate investment vehicles has broadened choices for all and the NAV REIT is flexible, scalable, open-ended and cost-efficient. Fund sponsors, fund managers, financial advisors, investors and even regulators could find food for thought in our analysis.